2005
DOI: 10.1177/154405910508400409
|View full text |Cite
|
Sign up to set email alerts
|

Initial Subgingival Colonization of ‘Pristine’ Pockets

Abstract: The treatment of periodontitis/peri-implantitis involves the reduction/eradication of periopathogens. After therapy, beneficial and pathogenic species recolonize the subgingival area. The dynamics of recolonization and especially the role of the supragingival environment in this process are still not well-understood. This prospective, split-mouth study followed the early colonization of 'pristine' pockets created during implant surgery (16 partially edentulous patients), to record the time needed before a comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
112
0
13

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(129 citation statements)
references
References 21 publications
4
112
0
13
Order By: Relevance
“…Early studies indicated absence of detection of Aggregatibacter actinomycetemcomitans and P. gingivalis, which could allude to the subgingival niche being their source (32, 33). However, later studies indicated that these taxa can be detected in peri-implantitis occurring in fully edentulous patients (11,16,34), indicating that they are not harbored solely in the subgingival region. This means that they are also found at other niches of the oral cavity, such as the soft tissues or saliva, and they are capable of colonizing the pristine implants or the peri-implant tissues of fully edentulous patients.…”
Section: Such As Staphylococcus Aureus Staphylococcus Epidermidis Ementioning
confidence: 99%
“…Early studies indicated absence of detection of Aggregatibacter actinomycetemcomitans and P. gingivalis, which could allude to the subgingival niche being their source (32, 33). However, later studies indicated that these taxa can be detected in peri-implantitis occurring in fully edentulous patients (11,16,34), indicating that they are not harbored solely in the subgingival region. This means that they are also found at other niches of the oral cavity, such as the soft tissues or saliva, and they are capable of colonizing the pristine implants or the peri-implant tissues of fully edentulous patients.…”
Section: Such As Staphylococcus Aureus Staphylococcus Epidermidis Ementioning
confidence: 99%
“…4 weeks) subgingival colonization, the frequency of detection of different species is similar between natural teeth and implants. Nevertheless, the colonization pattern on implants appears to be initially slower than on natural teeth (Quirynen et al 2005), given the pristine surfaces of the implant and the lack of the desired indigenous microbiota. The bacterial composition of the biofilm formed on implants closely resembles that of the 9 neighboring teeth (Botero et al 2005;Salvi et al 2008).…”
Section: Peri-implantitis As a Biofilm-initiated Diseasementioning
confidence: 99%
“…Studies about the development of biofilms on natural teeth showed that attachment of bacterial occurred within minutes and that the increase in specific species could be detected in a time period as short as 2-6 hours. It is likely that biofilm development on the implant follows a similar course and that maturation is well under way by 2 weeks as provided by Quirynen et al (4).…”
Section: Introduction the Development Of Biofilm On Implant Surfacesmentioning
confidence: 86%